2019
DOI: 10.1063/1.5113976
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent structures of shock-wave diffraction over 90° convex corner

Abstract: The turbulent structures and long-time flow dynamics of shock diffraction over 90 ○ convex corner associated with an incident shock Mach number Ms = 1.5 are investigated by large eddy simulation (LES). The average evolution of the core of the primary vortex is in agreement with the previous two dimensional studies. The Type-N wall shock structure is found to be in excellent agreement with the previous experimental data. The turbulent structures are well resolved and resemble those observed in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several numerical studies have been undertaken on shock diffraction in quiescent media covering a broad range of topics including vortices generated during diffraction (Murugan et al 2012;Reeves & Skews 2012;Dora et al 2014), turbulent structures (Soni et al 2019) and vorticity production (Sivier et al 1992;Tseng & Yang 2006). On numerous occasions, it has been demonstrated that viscous contributions may be neglected and many of the significant flow features associated with shock diffraction are sufficiently captured (Hillier 1991;Sun & Takayama 1997;Ripley, Lien & Yovanovich 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several numerical studies have been undertaken on shock diffraction in quiescent media covering a broad range of topics including vortices generated during diffraction (Murugan et al 2012;Reeves & Skews 2012;Dora et al 2014), turbulent structures (Soni et al 2019) and vorticity production (Sivier et al 1992;Tseng & Yang 2006). On numerous occasions, it has been demonstrated that viscous contributions may be neglected and many of the significant flow features associated with shock diffraction are sufficiently captured (Hillier 1991;Sun & Takayama 1997;Ripley, Lien & Yovanovich 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2014), turbulent structures (Soni et al. 2019) and vorticity production (Sivier et al. 1992; Tseng & Yang 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Chaudhuri et al [ 34 ] reported the stable shock capturing capabilities of explicit high-order DSEM in conjunction with entropy-generation-based artificial viscosity (AV) method. Although inviscid simulations quite accurately predict the shock wave diffraction wave patterns over different geometrical shapes, it is evident that viscous effects are important for resolving long-time behavior of shock-vortex evolution, shock-shear layer and shock-boundary layer interactions [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These issues are also discussed in the recent works [ 42 , 43 ] using high-order DSEM with AV method.…”
Section: Introductionmentioning
confidence: 99%